Fabrication of rectangular cross-sectional microchannels on PMMA with a CO2 laser and underwater fabricated copper mask. (1st September 2017) - Prakash, Shashi; Kumar, Subrata
Highlights: Rectangular and U-shape microchannels on PMMA were made possible with a CO2 laser processing. The suggested method was found to be precise and reliable apart from simplicity and cost effective. High degree of surface finish ensures the product to be readily used without requiring any post-processing. Underwater fiber laser based mask fabrication technique was found to be reliable and easy to adopt changes. Abstract: CO2 lasers are commonly used for fabricating polymer based microfluidic devices. Despite several key advantages like low cost, time effectiveness, easy to operate and no requirement of clean room facility, CO2 lasers suffer from few disadvantages like thermal bulging, improper dimensional control, difficulty to produce microchannels of other than Gaussian cross sectional shapes and inclined surface walls. Many microfluidic devices require square or rectangular cross-sections which are difficult to produce using normal CO2 laser procedures. In this work, a thin copper sheet of 40 μm was used as a mask above the PMMA (Polymethyl-methacrylate) substrate while fabricating the microchannels utilizing the raster scanning feature of the CO2 lasers. Microchannels with different width dimensions were fabricated utilizing a CO2 laser in with mask and without-mask conditions. A comparison of both the fabricating process has been made. It was found that microchannels with U shape cross section and rectangular cross-section can efficiently be produced using the with mask technique. In addition to this, this technique can provide perfect dimensional control and better surface quality of the microchannel walls. Such a microchannel fabrication process do not require any post-processing. The fabrication of mask using a nanosecond fiber laser has been discussed in details. An underwater laser fabrication method was adopted to overcome heat related defects in mask preparation. Overall, the technique was found to be easy to adopt and significant improvements were observed in microchannel fabrication.